2023
DOI: 10.1002/rse2.332
|View full text |Cite
|
Sign up to set email alerts
|

Accurate delineation of individual tree crowns in tropical forests from aerial RGB imagery using Mask R‐CNN

Abstract: Tropical forests are a major component of the global carbon cycle and home to two‐thirds of terrestrial species. Upper‐canopy trees store the majority of forest carbon and can be vulnerable to drought events and storms. Monitoring their growth and mortality is essential to understanding forest resilience to climate change, but in the context of forest carbon storage, large trees are underrepresented in traditional field surveys, so estimates are poorly constrained. Aerial photographs provide spectral and textu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…We used detectree2, a tool based on the Mask R-CNN deep learning architecture for automated tree crown delineation (Ball et al 2023), which has been shown to outperform another leading CNN method for tree crown detection (Gan, Wang, and Iio 2023).…”
Section: Automated Delineation and Fusion Of Results From Repeat Surveysmentioning
confidence: 99%
“…We used detectree2, a tool based on the Mask R-CNN deep learning architecture for automated tree crown delineation (Ball et al 2023), which has been shown to outperform another leading CNN method for tree crown detection (Gan, Wang, and Iio 2023).…”
Section: Automated Delineation and Fusion Of Results From Repeat Surveysmentioning
confidence: 99%
“…Schiefer et al [25] used the U-Net architecture to map tree species via semantic segmentation. Ball et al [13] developed Detectree2, an instance segmentation DCNN based on Facebook's Detectron2 architecture. While Schiefer et al [25] published their dataset and code, Deepforest and Detectree2 are publicly available Python packages, including pre-trained weights and pre-and post-processing steps.…”
Section: Supervised Deep Learning On Forest Datasetsmentioning
confidence: 99%
“…Overview papers such as Kattenborn et al [11] showed that very-high-resolution UAV data with a ground sampling distance (GSD) of below 2 cm and deep neural networks (DNNs) from the computer vision domain yield good results. For example, Gan et al [12] compared the widely used Python deep learning packages Detectree2 [13] and Deepforest [14] on different very-high-resolution GSDs. Xi et al [15] tested different dimensionality reductions to overcome the drawbacks of multispectral images for ITCD approaches, which can yield better results than just RGB-imagery.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Forest Structural Complexity Tool, used here to segment TLS trees, could work more efficiently with UAV data with additional training data (Krisanski et al, 2021). The recently released Segment Anything model (SAM; Kirillov et al, 2023) and Detectree2 (Ball et al, 2023), as well as multiple neural network applications based on the PointNet architecture (e.g. Wielgosz et al, 2023;Yu et al, 2022) show promise to accurately segment trees in 2D and 3D F I G U R E 5 Linear mixed models showing the relationship between cluster path length and cluster g cc in 35 healthy (solid line) and 85 infected (dashed line) trees.…”
Section: F I G U R Ementioning
confidence: 99%